Perancangan Pengendali Proportional-Integral Anti-Windup (Pi-Aw) pada Simulator Mobil Listrik untuk Kendali Kecepatan dan Torsi - Adnan Rafi Al Tahtawi; Arief Syaichu Rohman (ELECTRANS, 2016)
Proportional-Integral (PI) controller will be designed on electric car simulator for speed and torque control systems. The main components of this simulator are two direct current motors (DCMs) with a linked axis of rotation. Speed and torque control systems are designed for DCM 1 and DCM 2 which are represents the electric car and its load. PI controller is designed in three schemes: linear PI, PI with saturation and PI with anti-windup (PI-AW). The simulation result shows that the PI-AW scheme produces the best responses for speed and torque with control signals generated doesn’t exceed the saturation limit.